On the immature stages of Stethorus gilvifrons Mulsant (Coleoptera: Coccinellidae). - Mathur, L. M. L.; Srivastava, B. K. (Contributions to Entomology = Beiträge zur Entomologie, 1966)
A detailed morphological study of the immature stages of Stethorus gilvifrons Mulsant is presented. The illustrations include external distinguishing features of the egg, fourth instar larva and the pupa.